Critical Reflection as a Transformative Learning Approach in an Accounting Classroom: A Case Study of Accounting Education Pre-Service Teachers - Mhlongo, Favourite (CV Sinergi Ilmu dan Publikasi, 2025)
Attaining favorable student outcomes, including effective learning behaviors, skills, and attitudes that facilitate deep learning, is paramount for numerous universities globally. Research focusing on accounting students indicates that many encounter difficulties attaining the desired outcomes regardless of their degree program. Meanwhile, such outcomes are particularly vital in subjects like accounting, where fundamental understanding of knowledge must be obtained before its application. Among the factors that have emerged in the literature as influencing the achievement of desirable student outcomes in accounting are the approaches employed in teaching and learning the subject, one of which is reflective practice. However, there is a paucity of research examining the impact of reflective practice on the outcomes of accounting students, particularly pre-service teachers, as this population of accounting students remains underexplored, especially in developing nations such as South Africa. The present qualitative study followed a case study research design, employing a phenomenological approach to describe how a study sample of fifteen accounting students who were preservice teachers enrolled for a content knowledge-focused accounting module offered in the Bachelor of Education degree at one particular South African university experienced the application of the reflective practice and how it impacted their capacity to attain desired student outcomes in accounting. Employing content analysis and drawing on the reflective and transformative learning theories, this study's findings frame critical reflection employed in accounting education as a transformative approach for enhancing learning and achieving favorable outcomes for accounting students who are pre-service teachers. Critical reflection was found to have the potential to transform accounting students' learning behaviors, critical thinking dispositions, and attitudes, potentially supporting them to achieve better outcomes.